Students’ Critical Thinking Skills and Awareness of Industry 4.0: A Preliminary Study - Nurisyal Muhamad; Norhaninah Ab Gani; Suzilawati Uyob; Syatila Che Saruji (Journal of Human Development and Communication (JoHDeC), 2025)
Students should be ready to satisfy the requirement of industry 4.0 in account of future jobs. Industry 4.0 requires its staff to be critical in data analysis and capable of working flexibly across a variety of company situations. Moreover, the World Economic Forum survey on future job highlighted the importance of critical thinking and problem-solving skills for future employment. However, currently, most of the employers stressed on the graduates’ lack of critical thinking and problem-solving skills. Due to the fact that educational institution is a place to develop and enhance students’ critical thinking and problem-solving skills, therefore this study explores the level of Kolej Universiti Poly-Tech MARA Kuala Lumpur (KUPTM Kuala Lumpur) students’ critical thinking and problem-solving skills. This study also explores the students’ awareness of Industry 4.0 in order to understand their perspective of the future workplace. A sample of 170 students from KUPTM Kuala Lumpur completed the survey. The findings from this research help us to identify the level of our students’ critical thinking and problem-solving skills and their awareness about current industrial challenges. The findings also can be used for courses continuous improvement which to develop students with a higher capacity for reasoning and logical thinking. Students with a higher capacity to think critically will not only be appreciated as a workplace asset but will also have a bright future prospect.